Financial dimension of sports injuries, - Korkmaz, M., Kılıç, B., Çatıkkaş, F., Yücel, A. S. (My University, 2014)
A variety of sports injuries, which are unique to every branch of sports, can occur. Type of injury may vary depending on the branch of sports and the severity of the incidence. Wearing protective equipment minimizes the sports injuries. Injuries can also be prevented by avoiding practicing mistakes. Cost of medical treatment in sports injuries as well as lost working days could be regarded as an indicator of financial dimension of sports injuries. In this study, the importance of sports injuries, cost of these injuries, and financial dimension of sports injuries in terms of athletes will be tackled.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Injury; Sports; Financial Dimension; Equipment; Athlete